A Research Agenda for Environmental Policy Analysis: Past, Present, and Future - The National Level – Roundtable 1 - Jörgens, H. (Twenty-Eighth International Conference of Europeanists: The Environment of Democracy, 2022)
Since the late 1970s, research on environmental policy has constantly evolved into a major subfield of political science and policy analysis. Empirical work on topics of environmental policymaking is published not only in specialized journals but has become a key topic in all major political science, public administration, and international relations journals. This general trend has been reinforced by the rapid increase of public and scholarly attention to climate policy and the resulting increase in the amount of scholarly activity and publications dedicated to this subject. Currently environmental policy analysis is witnessing a rapid theoretical, conceptual and empirical development that makes it necessary to reflect on the state of the discipline. The two sessions of the roundtable bring together leading scholars in the field of environmental policy analysis to discuss the theoretical, conceptual, and empirical developments that have been made over the past year. What are the most important topics that environmental policy analysis needs to address in the next years? How can it contribute to better and more effective environment and climate policies? Which conceptual and methodological innovations carry the greatest potential to advance our understanding of the environmental policy process? While Part 1 focuses predominantly on national-level processes, Part 2 takes on a global perspective. The roundtable participants are authors of the forthcoming Routledge Handbook of Environmental Policy Analysis and will discuss some of the major findings of this comprehensive account of the past, present and future of environmental policy analysis.